Unit Cost Calculation of Indonesian National Health Insurance System (BPJS) Outpatient Care for Hypertension Diagnosis Patient in 2019 Over Harapan Keluarga Mataram Hospital - Moch Fuad Fuad; Yanuar Ramadhan; M. Reza Hilmy (Penerbit Kemala Indonesia, 2021)
Health financing often becomes an obstacle to accessibility of health services by the community. This situation especially occurs in situations where health financing must be borne by yourself (out of pocket) in the cash health service payment system (fee for service). Hypertension is a chronic disease that requires regular treatment and medication in daily basis. This causes a very high need of health services for hypertension patients. This study was a descriptive analysis using qualitative methods aimed to analyze unit costs of hypertension outpatients at Harapan Keluarga Hospital using the relative value unit (RVU) method. A total of 908 samples of hypertensive patients such as 292 (who used amlodipine and nifedipine), 64 (who used canderin, Abvask, and hyperil), 69 (who used concor and Abvask), 60 (who used hyperil, CPG, and Myonap), 67 (who used Abvask, CPG, and nifedipine), 55 (who used Abvask), 280 (who used amlodipine), 20 (who used nonprescription control). By this study, we can conclude that with a quality information system, top management can be helped in making the right decisions.